Carbon fibers modified with carbon nanoparticles by a facile and fast flame preparation for in-tube solid-phase microextraction - Qiong Jiang (Elsevier, 2022)
Carbon fibers (CFs) were modified with carbon nanoparticles (CNPs) by a facile and fast flame preparation method. CNPs-CFs were observed by scanning electron microscope, and the nano-scaled granular structure on the surface was found. This material was also characterized by Raman microscope and X-ray photoelectron spectroscope. It was placed into a polyetheretherketone tube to get an extraction tube, which was connected with high performance liquid chromatography for online analysis. The tube displayed the effective extraction to several polycyclic aromatic hydrocarbons (PAHs), based on the possible hydrophobic and π stacking mechanism. Under the optimized conditions (60 mL of sample volume, 2.00 mL min−1 of sample rate, 0.5% of methanol in sample, 2.0 min of desorption time), an analytical method towards these PAH targets was established. The low limits of detection (0.001–0.005 μg L−1), satisfactory linear ranges (0.003–5.0 μg L−1, 0.003–10.0 μg L−1) and efficient enrichment factors (1012–3164) were presented. The method was applied to detect trace targets in several water samples and satisfactory results were obtained. The method provided some superiorities over other analytical methods, like online test, shorter time and better sensitivity.